International intergovernmental and non-governmental organizations in international relations - Voronkov, Lev (EUT Edizioni Università di Trieste, 2018)
The article refers to the changes in the system of international relations that caused the emergence in the second half of the XIX century of international intergovernmental (IGOs) and non-governmental (INGOs) organizations and their subsequent evolution, notes the features and complementarity of each group of international organizations, assesses the League of Nations and the UN, as well as the impact of the cold war on the process ofemergence and functioning of international organizations and their transformation into tools for implementation of the collective strategy of member states against their international opponents, the emergence of a new type of international associations after its completion is noted, their distinctive features are highlighted. L’articolo considera i cambiamenti nel sistema di relazioni internazionaliche causarono l’emergenza nella seconda metà dell’Ottocento delle organizzazioni intergovernative internazionali (IGO) e delle organizzazioni non-governative internazionali (INGO) e la loro successiva evoluzione. Analizza le caratteristiche e la complementarietà di ciascun gruppo di organizzazioni internazionali, valuta la Lega delle Nazioni e l’ONU, così comel’impatto della guerra fredda sull’emergenza e il funzionamento delle organizzazioni internazionalie la loro trasformazione in strumenti per la realizzazione della strategia collettiva degli stati membri contro i loro oppositori internazionali. Viene infine considerata l’emergenza di un tipo di associazioni internazionali dopo il compimento delle loro funzioni, e vengono messe in risalto le caratteristiche specifiche.